Effects of entecavir on peripheral blood lymphocyte profiles in chronic hepatitis B patients with suboptimal responses to adefovir. (July 2014) - Zhang, Liwen; Wang, Quan; Zhao, Pingwei; Hu, Xiaoli; Jiang, Yanfang
Summary The aim of the present study was to assess the long‐term impact of entecavir (ETV) on T, B and natural killer (NK) cell immunity in patients with suboptimal responses to adefovir (SRA) chronic hepatitis B (CHB). Thirty SRA CHB patients and 20 age‐ and gender‐matched healthy controls (HC) completed at least 6 months of ETV treatment. Hepatitis B virus (HBV) DNA loads, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and the frequency of different subsets of T, B and NK cells in individual subjects were measured. There were smaller numbers of CD3–CD56+ and CD244+ NK cells, CD3+CD8+ T cells and cytokine‐secreting CD4+ T cells, but greater numbers of CD3+CD4+, CD4+CD25+Foxp3+, CD4+CD25+CD127low T cells and CD19+CD27+ B cells, detected in SRA patients. After switching to ETV monotherapy, the levels of HBV DNA and hepatitis B s antigen, as well as hepatitis B e antigen seropositivity, decreased gradually, accompanied by decreases in ALT and AST levels. Furthermore, the number of NK, CD8+ and cytokine‐secreting CD4+ T cells increased, whereas the number of CD4+, CD4+CD25+Foxp3+, CD4+CD25+CD127low T cells and CD19+CD27+ B cells decreased, in SRA CHB patients. The frequency of CD4+ interferon‐γ‐positive T cells was negatively associated with serum HBV DNA levels. Thus, treatment with ETV inhibits HBV replication, modulates T and NK cell immunity and improves liver function in SRA CHB patients.